Effect of Preservation Methods on Fat-Soluble Vitamins and Stress Biomarkers in Rhus coriaria L. (Sumac) of Different Regions - Ali, Haval Mohammed; Karatas, Fikret; Ozer, Dursun; Saydam, Sinan (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2024)
The number of fat-soluble vitamins and stress biomarkers in Rhus coriaria L. samples taken from different regions was determined by HPLC before and after being subjected to different preservation methods. For this purpose, one group of the samples was analyzed immediately, while the other two groups one of which oiled, and the other group is kept as is for six months. It was determined that the amounts of vitamin A, E, beta-carotene and lycopene in fresh sumac samples varied between 1.12 - 2.77, 84.40 - 230.65, 2.48 - 5.31 and 8.10 - 26.90 mu g (g dw)(-1), respectively. The highest loss of vitamins was observed in an unoiled group of samples. The amounts of GSH, GSSG, MDA, 4-HNE, and GSH/GSSG in the same samples varied between 1004.12 - 2550.42, 422.54 - 1375.38, 13.95 - 31.30, 7.12 - 15.40 mu g (g dw)(-1), and 1.16 - 3.49, respectively. While the amount of GSH and GSH/GSSG ratio in the stored sumac samples for six months decreased, on the other hand amount of MDA, GSSG, and 4-HNE increased. Differences in all examined parameters in fresh, unoiled, and oiled sumac samples are statistically significant (P<0.05). It was observed that the changes of the studied parameter in all sumac samples were lower in stored oiled samples.
Keywords: Rhus coriaria L.; Fat-soluble vitamins; Glutathione; Stress biomarkers